The Great Divide : Regional Inequality and Fiscal Policy - Gbohoui, William (IMF Working Papers; Working Paper, 2019)
Growing regional inequality within countries has raised the perception that 'some places and people' are left behind. This has prompted a shift toward inward-looking policies and away from pro-growth reforms. This paper presents novel stylized facts on regional inequality for OECD countries. It shows that regional disparity in per-capita GDP is large (even after adjusting for regional price differences), persistent, and widening over time. The paper also finds that rising nationwide income inequality is associated with both rising within-region income inequality and widening average income across regions. The rise in inequality is related to declining incentives for interregional labor mobility, especially for poor households in lagging regions, which are estimated to reduce by as much as one-third in the United States. Against these facts, the paper proposes a framework to identify whether, how and by whom fiscal policies can be used to tackle regional inequality. It outlines conditions under which those policies should be spatially-targeted and illustrates how they can be complementary to conventional means-testing methods in mitigating income inequality.